Kiev e Leopoli: Il 'testo' culturale - Brogi Bercoff, Giovanna; BARTOLINI, MARIA GRAZIA (Biblioteca di Studi Slavistici, 2007)
Kiev has always revealed a surprising capacity for assimilation, giving rise over time to multi-ethnic, multi-faith and multi-cultural contexts of various types. Thinking of the "Kiev text" leads inevitably to consideration of the other emblematic text of the Ukrainian identity, the no less composite reality of Lviv. This publication contains the contributions presented at a Conference (Milan, February 2007) addressed to the "cultural text" of Kiev and Lviv. The authors are specialists with different cultural profiles, and the book is of a deliberately inter-disciplinary character. In view of the richness and variety of the information it is offered, within the Italian and international context, as a useful source even for the non-specialist public, and is one of a very small number of books dedicated to Ukraine available in Italian. Clearly, the arguments addressed represent only a tiny part of the vast spectrum of issues and questions inherent to the specificity and plurality of Kiev and Lviv. The hope is that the seed sewn here will grow into further fruitful interest.